2001
DOI: 10.1634/stemcells.19-1-46
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Restriction Between Hematopoietic Stem Cells and Stromal Cells In Vitro

Abstract: We have previously found that a significant number of hematopoietic progenitors accumulate in engrafted bones with the same major histocompatibility complex (MHC) as the transplanted bone marrow cells. In the present study, to further clarify the MHC restriction between hematopoietic stem cells (HSC) and microenvironment, we carried out cobblestone colony formation assays by culturing HSCs with MHC-matched or -mismatched stromal cell monolayers. The formation of cobblestone colonies under MHC-mismatched stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 75 publications
0
37
0
Order By: Relevance
“…Since MHC class I molecules (but not MHC class II molecules) are expressed on both Lin -CD34 + cells and Am-Ad cells ( Figures 1A and 2B), it is conceivable that the MHC class I molecules are related to the MHC preference, as shown in mice: 22,23 the MHC preference is restricted by MHC class Ia molecules (but not MHC class Ib and II molecules) according to the results of cobblestone colony-forming assays in a co-culture system of B10 congenic mouse strains. 23 It can be speculated that putative unknown molecules reacting preferentially with self MHC class I molecules are expressed on HSC and/or MSC, and that the binding of MHC class I molecules and the putative MHC class I ligand induce stimulatory signal transductions and, as a result, induction of the expansion of the HSC. So far, CD8, class I receptors on natural killer cells (such as Ly49, p58 and NKB1) and PIR-A/B (paired immunoglobulin-like receptor) 31 are known ligands for MHC class I molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since MHC class I molecules (but not MHC class II molecules) are expressed on both Lin -CD34 + cells and Am-Ad cells ( Figures 1A and 2B), it is conceivable that the MHC class I molecules are related to the MHC preference, as shown in mice: 22,23 the MHC preference is restricted by MHC class Ia molecules (but not MHC class Ib and II molecules) according to the results of cobblestone colony-forming assays in a co-culture system of B10 congenic mouse strains. 23 It can be speculated that putative unknown molecules reacting preferentially with self MHC class I molecules are expressed on HSC and/or MSC, and that the binding of MHC class I molecules and the putative MHC class I ligand induce stimulatory signal transductions and, as a result, induction of the expansion of the HSC. So far, CD8, class I receptors on natural killer cells (such as Ly49, p58 and NKB1) and PIR-A/B (paired immunoglobulin-like receptor) 31 are known ligands for MHC class I molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our previous study in mice showed that cytokine messages (SCF, FLT-3L, and IL-6) are enhanced in the MHC-matched co-culture of HSC and fetal bone marrow-derived stromal cells. 23 It is difficult to explain the presence of MHC restriction and the quite long-term expansion of Lin -CD34 + cells on MHC-matched Am-Ad cells only by the enhanced production of GM-CSF. The formation of hematopoietic colonies in the MHC-matched co-culture system was significantly greater than that in the MHC-mismatched one ( Figure 5B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not preclude the possibility that, at a later stage of engraftment, antigen disparity, such as inhibition of allogeneic cobblestone formation in culture [42], may become relevant [4]. In this study, we partially corrected for fractional killing of antigen-disparate cells in the host reticuloendothelial system by increasing the size of allogeneic donor inoculum.…”
Section: Discussionmentioning
confidence: 99%
“…We found that stromal cells are essential for successful allogeneic BMT: stromal cells play a crucial role in preventing graft failure, 10,11 since there is a major histocompatibility complex (MHC) restriction between hematopoietic stem cells (HSC) and stromal cells. 2,3 In order to prevent the recurrence of autoimmune diseases in MRL/lpr mice, we therefore carried out BMT plus bone grafts to replace not only hematopoietic cells but also stromal cells with donor cells. MRL/lpr mice that had been irradiated (8.5Gy) and then reconstituted with C57BL/6 bone marrow cells (BMC) plus bone grafts survived more than 48 weeks.…”
mentioning
confidence: 99%